Co-bots to improve occupational health and safety: preliminary analysis and integration proposal at Dana-Transejes, Colombia - Daniela Bellon-Monsalve; Jossie Esteban Garzon-Baquero; Pablo Andrés Pérez-Gutiérrez (AiBi Revista de Investigación, Administración e Ingeniería)
The adoption of advanced technologies, such as automation and robotics, is crucial in the era of Industry 4.0 for optimizing industrial processes. This article presents a detailed analysis and integration proposal of a collaborative robot (Co-BOT) at the DANA-Transejes production plant, focusing on improving occupational health and safety for operators while increasing operational efficiency. The methodology employed follows a mixed-methods approach, combining the characterization of the current process with qualitative and quantitative data provided by the company, along with direct observations. This characterization identified operational inefficiencies and ergonomic risks related to the manual handling of heavy loads. Based on these findings, a proposal for Co-BOT implementation was developed, detailing technical, operational, and economic aspects of the integration. The estimated results project a 15% reduction in production cycle times, an increase of 375 additional boxes per year, and a significant improvement in safety, reducing the risk of work-related injuries by 100% for specific tasks. Moreover, a reduction in costs due to recovery breaks and medical leaves is expected, contributing to an annual economic saving of approximately $23,950 USD. This study demonstrates the feasibility of implementing Co-BOTs in Latin American industrial environments, highlighting their potential as a cost-effective solution for improving competitiveness and operational sustainability in regions with limited investment in technological innovation.